2010
DOI: 10.1091/mbc.e10-03-0255
|View full text |Cite
|
Sign up to set email alerts
|

KHDC1B Is a Novel CPEB Binding Partner Specifically Expressed in Mouse Oocytes and Early Embryos

Abstract: The expression and activities of two members of a novel KH domain protein family were tested. KHDC1A and 1B are highly expressed in oocytes. Based on ectopic expression, KHDC1A regulates apoptosis whereas 1B interacts with the cytoplasmic polyadenylation machinery. KHDC1B may serve as a translational repressor during oocyte maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 50 publications
(65 reference statements)
1
16
0
Order By: Relevance
“…Mammalian species have no comparable ortholog to maskin; the mammalian TACC3 gene codes for a protein similar to Xenopus maskin, but lacks the EIF4E binding domain (de Moor et al, ). Nevertheless, recent findings have pointed towards alternative models of translational repression that are maskin‐independent (Minshall et al, ; Cai et al, ; Tomek and Wollenhaupt ), and the expression pattern of CP‐associated genes observed herein is consistent with the activity of such post‐transcriptional regulatory mechanisms during bovine oocyte maturation.…”
Section: Discussionsupporting
confidence: 77%
“…Mammalian species have no comparable ortholog to maskin; the mammalian TACC3 gene codes for a protein similar to Xenopus maskin, but lacks the EIF4E binding domain (de Moor et al, ). Nevertheless, recent findings have pointed towards alternative models of translational repression that are maskin‐independent (Minshall et al, ; Cai et al, ; Tomek and Wollenhaupt ), and the expression pattern of CP‐associated genes observed herein is consistent with the activity of such post‐transcriptional regulatory mechanisms during bovine oocyte maturation.…”
Section: Discussionsupporting
confidence: 77%
“…KHDC3L codes for a KH-domain containing protein, of which another member, KHDC1B, has been shown to bind mRNA and is believed to play a role in the regulation of their translation during oocyte maturation. 23 The closest NLRP gene to NLRP7 is NLRP2, which is located 25-kb distal to NLRP7 on human chromosome 19q13.4 in a head-to-head orientation. NLRP7 does not have rodent or bovine orthologues and is believed to have originated from a common NLRP2/7 ancestor in primates.…”
Section: Introductionmentioning
confidence: 99%
“…Maskin is a prime example of a species‐specific difference, as mammalian TACC3 lacks the eIF4E binding domain, suggesting an alternate protein or modified translational regulatory system may exist in mammals. Indeed, recent advances have revealed the potential for Maskin‐independent translational regulation . In mice, KH‐domain containing 1A ( Khdc1a ) and KH‐domain containing 1B ( Khdc1b ) were found to be expressed and translated in mouse oocytes, one of which is capable of binding eIF4e and CPEB .…”
Section: Mammalian Species Express Cp‐associated Factorsmentioning
confidence: 99%
“…40, 65 -69 In mice, KH-domain containing 1A (Khdc1a) and KH-domain containing 1B (Khdc1b) were found to be expressed and translated in mouse oocytes, one of which is capable of binding eIF4e and CPEB. 66 Alternatively, another protein containing a coiled-coil domain resembling TACC3 was discovered in cow oocytes, termed Maskin-like, and found not to bind CPEB but able to bind eIF4e preventing cap-binding. 65 Although KHDC1 and Maskin-like proteins are potential Maskin alternatives, further studies are required to elucidate their function in relation to gene-specific regulation and whether these proteins are conserved in other mammals.…”
Section: Figure 2 | Expression Of Polyadenylation and Translationalmentioning
confidence: 99%